Science for kids 39 easy geography activities - Wood, Robert W. 1933- (Wood, Robert W. 1933- Science for kids series. ., 1991)
Introduces the science of geography through thirty-nine activities, including "Finding North by the Sun," "Making a Compass," and "Neighborhood Research."